2013
DOI: 10.1093/humrep/det118
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and obstetric outcomes after radical abdominal trachelectomy for early-stage cervical cancer in a series of 31 pregnancies

Abstract: Prospective multicenter studies are needed to determine if the results shown in this retrospective cohort can be generalized to all patients with early-stage cervical cancer who wish to undergo the fertility-sparing RAT procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 17 publications
1
39
0
2
Order By: Relevance
“…In a study of patients undergoing abdominal trachelectomy, only 36.2% of patients subsequently conceived. 4 In women who conceive following trachelectomy, pregnancy may be associated with adverse outcomes, most notably preterm delivery. In a review of 200 pregnancies after radical trachelectomy, Jolley et al showed that 9.5% (19/ 200) pregnancies ended in second-trimester miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients undergoing abdominal trachelectomy, only 36.2% of patients subsequently conceived. 4 In women who conceive following trachelectomy, pregnancy may be associated with adverse outcomes, most notably preterm delivery. In a review of 200 pregnancies after radical trachelectomy, Jolley et al showed that 9.5% (19/ 200) pregnancies ended in second-trimester miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that radical vaginal trachelectomy has better reproductive outcomes than abdominal trachelectomy [3,[6][7][8][9]. The mechanistic reasons for this superiority remain unclear, but less invasive approaches preserving much more tissue and nerves around the cervix may contribute.…”
Section: Commentsmentioning
confidence: 99%
“…Patients with FIGO stage Ia2-Ib1 with small tumor size (less than 2 cm in diameter) without retroperitoneal lymph node metastases have been likely to undergo this operation, and the oncologic outcomes have been reported to be satisfactory, comparable with radical hysterectomy [3][4][5]. However, the reproductive outcomes of this operation appear insufficient, and some reports indicated that radical vaginal trachelectomy, rather than abdominal trachelectomy, shows more favorable reproductive outcomes [3,[6][7][8][9], while the oncologic outcomes of vaginal trachelectomy appeared to be inferior to those of the abdominal procedure, especially in patients with tumors larger than 2 cm [8,[10][11][12]. The precise cause of the relatively poor reproductive outcomes of abdominal radical trachelectomy remains unclear, but it is possible that disruption of autonomic nerves that innervate the uterine Objectives: Nerve-sparing techniques to avoid bladder dysfunction in abdominal radical hysterectomy have been established during the past two decades, and they have been applied to radical trachelectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Несколько большая частота наступления беременностей отмечена в исследо-вании H. Nishio и соавт. [4], в котором авторы, исследуя исходы 114 РАТ, выявили, что беременность наступила у 25 (21,9%) пациенток, однако из 11 469 женщин планиро-вали беременность. Таким образом, частота наступления беременности в данном исследовании составила 36,2%.…”
unclassified
“…В исследовании Японских авторов [4], изучавших от-даленные результаты РАТ, было отмечено, что беремен-ность наступила у 25 (36,2%) из 69 пациенток, желавших реализовать репродуктивную функцию. Из 25 пациенток у 4 (16%) беременность прервалась в I триместре.…”
unclassified